An integrated framework to support remote IEEE 1149.1 /1149.4 design for test experiments - José M. M. Ferreira (2006)
Remote experiments for academic purposes can only achieve their educational goals if an appropriate framework is able to provide a basic set of features, namely remote laboratory management, collaborative learning tools and content management and delivery. This paper presents a framework developed to support remote experiments in a design for test class offered to final year students at the Electrical and Computer Engineering degree at the University of Porto. The proposed solution combines a test language command interpreter and various virtual instruments (VIs), with a demonstration board that comprises a boundary-scan IEEE 1149.1 / 1149.4 test infrastructure. The experiments are presented as embedded learning objects, with no distinction from other e-learning contents (e.g. lessons, lecture notes, etc.).